Dinge als Herausforderung Kontexte, Umgangsweisen und Umwertungen von Objekten - Hahn, Hans Peter; Neumann, Friedemann (Edition Kulturwissenschaft, 2018)
Things are not as nonpolitical as they seem: This book illuminates the hidden meanings and ambiguities of objects - an important contribution to the research on material everyday culture!